Advances in the Treatment of Polycythemia Vera: Trends in Disease Management - Arya, Yajur (Cureus, 2021)
Treatment modalities for polycythemia vera (PV) have evolved over time. Phlebotomy and low-dose aspirin suffice in low-risk patients, but cytoreductive therapies are indicated in all high-risk patients (age ≥ 65 years or those with a history of PV-related thrombotic event) and may be considered for low-risk patients with progressively increasing splenomegaly, progressively increasing leucocyte and platelet counts, and for those who do not tolerate phlebotomy. Hydroxyurea/hydroxycarbamide or interferons can be used as first-line drugs. Hydroxyurea may not be tolerated by some patients, and it also carries risk of myelosuppression. Interferon alfa is especially useful for PV symptoms, and the newer preparation, ropeginterferon alfa-2b, has lesser incidence of flu-like reactions. Ruxolitinib reduces the JAK2V617F mutation burden and is used as a second-line drug. Anagrelide reduces platelet production and can be used in conjunction with hydroxyurea in patients with excessive thrombocytosis. The alkylating agent, busulfan, can also be used as a last resort in patients with a limited life expectancy. Prospective future treatments include givinostat, a histone deacetylase inhibitor, and idasanutlin, a murine double minute 2 antagonist.